Efficacy and acceptability of the vaginal combination hormone system containing ethinylestradiol and etonogestrel. Literature rewiev - Elena A Mezhevitinova; Vera N Prilepskaya (IP Berlin A.V., 2019)
The review focuses on evaluating the effectiveness and acceptability of a vaginal ring and combined oral contraceptives (COC) in a comparative aspect. It is shown that the vaginal ring has high efficiency, comparable to COC, has better cycle control, fewer side effects, is convenient to use, there is no need for daily monitoring of the pill.